Determinan Ketimpangan Distribusi Pendapatan di Karesidenan Malang Tahun 2015-2019 - Yery Arif Ramadhan Ramadhan; Sulistyono Setyo Wahyu (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This research examines the effect of the total population, minimum wages, and economic growth against income distribution inequality. The object in the study is a residency of Malang. The research used secondary data in 2015-2019 obtained from the Central Bureau of Statistics Republic of Indonesia. The data analysis technique in this research used the panel data regression analysis. The results indicate that total population and minimum wages significantly influence income distribution inequality, while economic growth has no impact on income distribution inequality.